The Impacts of Deceptive Advertising on Women Consumer - Newaz, Nafisa (European Scientific Journal, ESJ, 2017)
Every day, consumers are exposed to hundreds of commercial messages. The ultimate goal of advertising is to robustly attract consumers by giving them product-related information, application of the products, demonstrate the uses of the products, and guide them to purchase the products. It is absolutely necessary to ensure that consumers perceive advertising as something positive and not otherwise. Consumers’ positive attitudes towards advertising can generate profit for companies, and that is only if advertising can promote products that the consumers needs. Advertising should follow ethical guidelines. Some actions that are quite unethical include women exploitation, influencing consumers to buy a product without providing them with adequate knowledge on what is to be bought, and deceptive advertising, involving false claims and other issues which could lead to moral deterioration of the society. This paper is an effort to find out the impacts of these types of deceptive advertisements on women.